Pomiędzy prawem a systemem ie – aborcja w Japonii - Molik, Karolina (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
Abortion is a very controversial topic in Poland. Its legality and the restrictions thereof are divisive for both the academic circles and laypeople. Is the situation similar in Japan? What is the origin of the current legislation? Are the regulations different from those in Poland? How so, if yes? This presentation will analyze the legal conditions for abortion in Japan. Both medical and legal aspects will be discussed. Furthermore the Author will try to draw a correlation between a high abortion rate and the attitude towards birth control. Where does abortion fit within the ie system?
Keywords: abortion; Japan; mizuko; family; laws on protection of motherhood